A Review of the Current Research Status of Graphene for the Removal of Microplastics and Antibiotics from Water - Gao, Yifei (International Journal of Natural Resources and Environmental Studies, 2024)
As highly representative pollutants among emerging pollutants, antibiotics and microplastics are characterized by strong bioaccumulation, difficult degradation, and high toxicity, and along with the increasing use, the crisis of synergy between the two is increasing. Graphene, a material with high specific surface area and high reactivity, has a wide range of application prospects in the field of water treatment, especially graphene oxide and graphene composites make the application of this material has a certain diversity. The research on graphene and its composites in water membrane treatment and catalytic degradation for the removal of microplastics and antibiotics in recent years is reviewed to explore the research trends and hotspots, and to explore the research prospects.